Composite fiber fabric type water electrolysis separator and method for manufacturing the same

CN116732571BActive Publication Date: 2026-10-30ZHEJIANG ZHENGBEN NEW MATERIALS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310650518.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-04
Publication Date
2026-10-30
Estimated Expiration
2043-06-04

AI Technical Summary

Technical Problem

[0005]隔膜布是水电解槽的主要核心材料,水电解制氢、制氧设备又广泛用于军事、石化、钢铁等制造领域,目前主要的碱性水电解制氢设备厂家仍然使用石棉布作为隔膜,但是,石棉它的最大危害来自于它的纤维,这是一种非常细小、肉眼几乎看不见的纤维,当这些细小的纤维释放以后,会长时间浮游于空气中,容易被人体吸入,对人体健康产生较大的威胁

Benefits of technology

本发明的通过采用皮芯复合聚苯硫醚纤维制成水电解隔膜,其亲水性能得到大幅度的提高,能够在电解液中进行快速润湿,从而使得电解液中的离子能够顺利的通过;通过皮芯复合聚苯硫醚纤维的芯束部分采用纯聚苯硫醚制成,能够有效的保证了水电解隔膜具有足够的机械强度,而现有技术中采用完全掺入填料的聚苯硫醚纤维,由于填料的引入,会造成其强度性能明显降低,而当强度性能降低一定幅度后,会造成水电解隔膜的使用寿命大幅度的缩短,同时,为了提高聚苯硫醚纤维的亲水性,现有技术通过引入特定填料来提高聚苯硫醚纤维的亲水性,进而提高水电解隔膜的亲水性,但是,一来,掺入特定填料后,制成的水电解隔膜的强度会有一定的损失,其次,由于特定填料的成本较为昂贵,大量添加,会造成成本具有明显的抬高,而本发明制备的纳米复合料具有更好的亲水性,并且通过采用皮芯复合聚苯硫醚纤维,不仅降低了填料的引入量,节约了成本,同时,由于芯束采用了纯聚苯硫醚树脂制成,其强度性能得到了有效的保证。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The application relates to the technical field of water electrolysis diaphragms, and discloses a composite fiber fabric type water electrolysis diaphragm and a preparation method thereof, which is formed by spinning core-sheath composite polyphenylene sulfide fibers; the core-sheath composite polyphenylene sulfide fiber comprises a core bundle and a skin layer, and the mass ratio of the core bundle to the skin layer is 3:1; wherein the core-sheath composite polyphenylene sulfide fiber is formed by double-component melt spinning; the water electrolysis diaphragm is made of the core-sheath composite polyphenylene sulfide fiber, the hydrophilic property of the water electrolysis diaphragm is greatly improved, the water electrolysis diaphragm can be quickly wetted in an electrolyte, so that ions in the electrolyte can smoothly pass through; the core bundle part of the core-sheath composite polyphenylene sulfide fiber is made of pure polyphenylene sulfide, so that the water electrolysis diaphragm can effectively have sufficient mechanical strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of water electrolysis membrane technology, specifically to a composite fiber fabric type water electrolysis membrane and its preparation method. Background Technology

[0002] In recent years, the massive consumption of petroleum energy worldwide has made the energy crisis a major challenge facing countries around the world. Countries are searching for reliable new energy sources to address this crisis. Hydrogen energy is a highly efficient, clean, and pollution-free energy source in modern society, aligning with the theme of green development. It is receiving increasing attention from countries worldwide, making the development of hydrogen energy of significant strategic importance.

[0003] Hydrogen production technology through water electrolysis has a history of over two hundred years, and has seen significant advancements in recent decades. Water electrolysis has become one of the most important methods for large-scale hydrogen production worldwide.

[0004] Hydrogen and oxygen produced by water electrolysis are separated by a diaphragm in the electrolytic cell. The function of the diaphragm is to prevent the products at the two electrodes from mixing, while its presence must not interfere with the migration of ions in the solution between the two electrodes.

[0005] Diaphragm cloth is the main core material of water electrolysis cells. Water electrolysis hydrogen and oxygen production equipment is also widely used in military, petrochemical, steel and other manufacturing fields. At present, the main manufacturers of alkaline water electrolysis hydrogen production equipment still use asbestos cloth as diaphragm. However, the greatest danger of asbestos comes from its fibers, which are very fine fibers that are almost invisible to the naked eye. When these fine fibers are released, they will float in the air for a long time and are easily inhaled by the human body, posing a great threat to human health.

[0006] Based on this, we propose a composite fiber fabric type water electrolysis membrane in order to address the shortcomings of existing technologies. Summary of the Invention

[0007] (a) Technical problems to be solved To address the shortcomings of existing technologies, this invention provides a composite fiber fabric type water electrolysis diaphragm and its preparation method.

[0008] (II) Technical Solution To achieve the above objectives, the present invention provides the following technical solution: A composite fiber fabric type water electrolysis membrane is made of core-sheath composite polyphenylene sulfide fiber through weaving. The core-sheath composite polyphenylene sulfide fiber includes a core bundle and a sheath layer, wherein the mass ratio of the core bundle to the sheath layer is 3:1. The core-sheath composite polyphenylene sulfide fiber is formed by two-component melt spinning. The core bundle is made of polyphenylene sulfide resin; The skin layer is made of nano-modified polyphenylene sulfide resin.

[0009] As a further technical solution, the method for preparing the nano-modified polyphenylene sulfide resin is as follows: (1) First, prepare a hexadecyltrimethylammonium bromide solution; (2) Add 16-20g of nano silica to 50-54mL of cetyltrimethylammonium bromide solution, stir for 10min at room temperature, and then sonicate for 5min to obtain a dispersion. (3) Mix 38-40g of polydimethylsiloxane, 13-15g of hydrogen-containing silicone oil and 1-1.5g of graphene, stir and mix at 1200r / min for 20min at 60℃, cool to obtain the mixture; (4) Add the dispersion and the mixture to the reactor at a mass ratio of 1.2:1, keep warm and stir for 10 min, then add 0.2-0.3 g of catalyst, adjust the temperature to 50℃ under an inert atmosphere, continue stirring and reacting for 20 hours, then filter, wash and dry to obtain nanocomposite material; (5) The nanocomposite material, coupling agent and polyphenylene sulfide resin obtained above are mixed and then added to a twin-screw extruder for melt extrusion granulation to obtain nano-modified polyphenylene sulfide resin.

[0010] As a further technical solution, the concentration of the hexadecyltrimethylammonium bromide solution in step (1) is 0.35-0.4 mol / L.

[0011] As a further technical solution: the frequency of the ultrasonic wave in step (2) is 40kHz.

[0012] As a further technical solution: the catalyst in step (4) is a chloroplatinic acid catalyst; The inert atmosphere is a nitrogen atmosphere.

[0013] As a further technical solution, the inert gas in step (4) is nitrogen.

[0014] As a further technical solution, the mass fraction of nanocomposite material in the nano-modified polyphenylene sulfide resin in step (5) is 1-1.8%; The coupling agent has a mass fraction of 0.2-0.3%; The coupling agent is vinyltrimethoxysilane.

[0015] In step (3), graphene can also be replaced with nano-alumina or nano-zirconia. When nano-alumina or nano-zirconia is used, the strength performance will be reduced slightly compared to graphene, but the reduction is limited. A method for preparing a composite fiber fabric type water electrolysis separator includes metering, opening and mixing, carding into a web, hydroentangling the front and back sides of the web, drying, and winding to obtain a composite fiber fabric type water electrolysis separator. Hydroentangling pressure 150-200 bar; The weight of composite fiber fabric type water electrolysis diaphragm is 180-250 grams per square meter.

[0016] The maximum pore size of the composite fiber fabric type water electrolysis membrane is 10-30μm, with 85.0-97.0% having a pore size below 10μm and the remainder having a pore size above 10μm, including 10μm.

[0017] (III) Beneficial Effects Compared with the prior art, the present invention provides a composite fiber fabric type water electrolysis membrane, which has the following beneficial effects: This invention utilizes a core-sheath composite polyphenylene sulfide fiber to fabricate a water electrolysis membrane, significantly improving its hydrophilicity and enabling rapid wetting in the electrolyte, thus facilitating the passage of ions. Furthermore, the core bundle of the core-sheath composite polyphenylene sulfide fiber is made of pure polyphenylene sulfide, effectively ensuring sufficient mechanical strength for the water electrolysis membrane. In contrast, existing technologies use polyphenylene sulfide fibers completely incorporating fillers, which significantly reduces strength due to the filler introduction. This reduction in strength drastically shortens the lifespan of the water electrolysis membrane. Additionally, to improve the hydrophilicity of the polyphenylene sulfide fiber... To improve the hydrophilicity of polyphenylene sulfide (PPS) fibers, existing technologies have introduced specific fillers to enhance the hydrophilicity of PPS fibers, thereby improving the hydrophilicity of the water electrolysis membrane. However, firstly, the strength of the water electrolysis membrane is somewhat reduced after incorporating specific fillers. Secondly, since specific fillers are relatively expensive, adding large amounts will significantly increase the cost. The nanocomposite material prepared in this invention has better hydrophilicity, and by using a core-sheath composite PPS fiber, not only is the amount of filler introduced reduced, saving costs, but also the strength performance is effectively guaranteed because the core bundle is made of pure PPS resin. Detailed Implementation

[0018] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0019] The following are specific examples: Example

[0020] A composite fiber fabric type water electrolysis membrane is made of core-sheath composite polyphenylene sulfide fiber through weaving. The core-sheath composite polyphenylene sulfide fiber includes a core bundle and a sheath layer, wherein the mass ratio of the core bundle to the sheath layer is 3:1. The core-sheath composite polyphenylene sulfide fiber is formed by two-component melt spinning. The core bundle is made of polyphenylene sulfide resin; The skin layer is made of nano-modified polyphenylene sulfide resin. The preparation method of the polybutylene terephthalate stretching hot plate temperature is 70°C, the hot plate temperature is 130°C, and the stretching ratio is 2.5 nano-modified polyphenylene sulfide resin is as follows: (1) First, prepare a hexadecyltrimethylammonium bromide solution; the concentration of the hexadecyltrimethylammonium bromide solution is 0.35 mol / L.

[0021] (2) Add 16g of nano-silica to 50mL of cetyltrimethylammonium bromide solution, stir for 10min at room temperature, and then sonicate for 5min to obtain a dispersion; the frequency of the ultrasonic wave is 40kHz.

[0022] (3) Mix 38g of polydimethylsiloxane, 13g of hydrogen-containing silicone oil and 1g of graphene, stir and mix at 1200r / min for 20min at 60℃, cool to obtain the mixture; (4) Add the dispersion and the mixture to the reactor at a mass ratio of 1.2:1, keep warm and stir for 10 min, then add 0.2 g of chloroplatinic acid catalyst, adjust the temperature to 50 °C under nitrogen atmosphere protection, continue stirring for 20 hours, then filter, wash and dry to obtain nanocomposite material; (5) The nanocomposite material, vinyltrimethoxysilane, and polyphenylene sulfide resin obtained above are mixed and then added to a twin-screw extruder for melt extrusion granulation to obtain nano-modified polyphenylene sulfide resin; the mass fraction of nanocomposite material in nano-modified polyphenylene sulfide resin is 1%; The vinyltrimethoxysilane has a mass fraction of 0.2%; A method for preparing a composite fiber fabric type water electrolysis separator includes metering, opening and mixing, carding into a web, hydroentangling the front and back sides of the web, drying, and winding to obtain a composite fiber fabric type water electrolysis separator. 150 bar pressure for hydroentangling; The weight of the composite fiber fabric type water electrolysis diaphragm is 210.4 grams per square meter.

[0023] It operates at a working temperature of 90℃, with a potassium hydroxide electrolyte of 25% by mass, a DC voltage of 3.5V, and a DC current of 750A for hydrogen electrolysis, and can operate continuously for more than 800 hours. Example

[0024] A composite fiber fabric type water electrolysis membrane is made of core-sheath composite polyphenylene sulfide fiber through weaving. The core-sheath composite polyphenylene sulfide fiber includes a core bundle and a sheath layer, wherein the mass ratio of the core bundle to the sheath layer is 3:1. The core-sheath composite polyphenylene sulfide fiber is formed by two-component melt spinning. The core bundle is made of polyphenylene sulfide resin; The skin layer is made of nano-modified polyphenylene sulfide resin.

[0025] The preparation method of nano-modified polyphenylene sulfide resin is as follows: (1) First, prepare a hexadecyltrimethylammonium bromide solution; the concentration of the hexadecyltrimethylammonium bromide solution is 0.36 mol / L.

[0026] (2) Add 18g of nano-silica to 52mL of cetyltrimethylammonium bromide solution, stir for 10min at room temperature, and then sonicate for 5min to obtain a dispersion; the frequency of the ultrasound is 40kHz.

[0027] (3) Mix 39g of polydimethylsiloxane, 14g of hydrogen-containing silicone oil and 1.2g of graphene, stir and mix at 1200r / min for 20min at 60℃, cool to obtain the mixture; (4) Add the dispersion and the mixture to the reactor at a mass ratio of 1.2:1, keep warm and stir for 10 min, then add 0.22 g of chloroplatinic acid catalyst, adjust the temperature to 50 °C under nitrogen atmosphere protection, continue stirring and react for 20 hours, then filter, wash and dry to obtain nanocomposite material; (5) The nanocomposite material, vinyltrimethoxysilane, and polyphenylene sulfide resin obtained above are mixed and then added to a twin-screw extruder for melt extrusion granulation to obtain nano-modified polyphenylene sulfide resin; the mass fraction of nanocomposite material in the nano-modified polyphenylene sulfide resin is 1.3%; The vinyltrimethoxysilane has a mass fraction of 0.25%; A method for preparing a composite fiber fabric type water electrolysis separator includes metering, opening and mixing, carding into a web, hydroentangling the front and back sides of the web, drying, and winding to obtain a composite fiber fabric type water electrolysis separator. 165 bar pressure for hydroentangling; The weight of the composite fiber fabric type water electrolysis diaphragm is 210.5 grams per square meter.

[0028] It operates at a working temperature of 90℃, with a potassium hydroxide electrolyte of 25% by mass, a DC voltage of 3.5V, and a DC current of 750A, and can operate continuously for more than 840 hours. Example

[0029] A composite fiber fabric type water electrolysis membrane is made of core-sheath composite polyphenylene sulfide fiber through weaving. The core-sheath composite polyphenylene sulfide fiber includes a core bundle and a sheath layer, wherein the mass ratio of the core bundle to the sheath layer is 3:1. The core-sheath composite polyphenylene sulfide fiber is formed by two-component melt spinning. The core bundle is made of polyphenylene sulfide resin; The skin layer is made of nano-modified polyphenylene sulfide resin.

[0030] The preparation method of nano-modified polyphenylene sulfide resin is as follows: (1) First, prepare a hexadecyltrimethylammonium bromide solution; the concentration of the hexadecyltrimethylammonium bromide solution is 0.38 mol / L.

[0031] (2) Add 18g of nano-silica to 53mL of cetyltrimethylammonium bromide solution, stir for 10min at room temperature, and then sonicate for 5min to obtain a dispersion; the frequency of the ultrasonic wave is 40kHz.

[0032] (3) Mix 39g of polydimethylsiloxane, 14g of hydrogen-containing silicone oil and 1.4g of graphene, stir and mix at 1200r / min for 20min at 60℃, cool to obtain the mixture; (4) Add the dispersion and the mixture to the reactor at a mass ratio of 1.2:1, keep warm and stir for 10 min, then add 0.28 g of chloroplatinic acid catalyst, adjust the temperature to 50 °C under nitrogen atmosphere protection, continue stirring and react for 20 hours, then filter, wash and dry to obtain nanocomposite material; (5) The nanocomposite material, vinyltrimethoxysilane, and polyphenylene sulfide resin obtained above are mixed and then added to a twin-screw extruder for melt extrusion granulation to obtain nano-modified polyphenylene sulfide resin; the mass fraction of nanocomposite material in the nano-modified polyphenylene sulfide resin is 1.5%; The vinyltrimethoxysilane has a mass fraction of 0.28%; A method for preparing a composite fiber fabric type water electrolysis separator includes metering, opening and mixing, carding into a web, hydroentangling the front and back sides of the web, drying, and winding to obtain a composite fiber fabric type water electrolysis separator. 180 bar of hydroentangling pressure; The weight of the composite fiber fabric type water electrolysis diaphragm is 211.8 grams per square meter.

[0033] It operates at a working temperature of 90℃, with a potassium hydroxide electrolyte of 25% by mass, a DC voltage of 3.5V, and a DC current of 750A, and can operate continuously for more than 730 hours. Example

[0034] A composite fiber fabric type water electrolysis membrane is made of core-sheath composite polyphenylene sulfide fiber through weaving. The core-sheath composite polyphenylene sulfide fiber includes a core bundle and a sheath layer, wherein the mass ratio of the core bundle to the sheath layer is 3:1. The core-sheath composite polyphenylene sulfide fiber is formed by two-component melt spinning. The core bundle is made of polyphenylene sulfide resin; The skin layer is made of nano-modified polyphenylene sulfide resin.

[0035] The preparation method of nano-modified polyphenylene sulfide resin is as follows: (1) First, prepare a hexadecyltrimethylammonium bromide solution; the concentration of the hexadecyltrimethylammonium bromide solution is 0.4 mol / L.

[0036] (2) Add 20g of nano silica to 54mL of cetyltrimethylammonium bromide solution, stir for 10min at room temperature, and then sonicate for 5min to obtain a dispersion; the frequency of the ultrasonic wave is 40kHz.

[0037] (3) Mix 40g of polydimethylsiloxane, 15g of hydrogen-containing silicone oil and 1.5g of graphene, stir and mix at 1200r / min for 20min at 60℃, cool to obtain the mixture; (4) Add the dispersion and the mixture to the reactor at a mass ratio of 1.2:1, keep warm and stir for 10 min, then add 0.3 g of chloroplatinic acid catalyst, adjust the temperature to 50°C under nitrogen atmosphere protection, continue stirring for 20 hours, then filter, wash and dry to obtain nanocomposite material; (5) The nanocomposite material, vinyltrimethoxysilane, and polyphenylene sulfide resin obtained above are mixed and then added to a twin-screw extruder for melt extrusion granulation to obtain nano-modified polyphenylene sulfide resin; the mass fraction of nanocomposite material in the nano-modified polyphenylene sulfide resin is 1.8%; The vinyltrimethoxysilane has a mass fraction of 0.3%; A method for preparing a composite fiber fabric type water electrolysis separator includes metering, opening and mixing, carding into a web, hydroentangling the front and back sides of the web, drying, and winding to obtain a composite fiber fabric type water electrolysis separator. 200 bar pressure for hydroentangling; The weight of the composite fiber fabric type water electrolysis diaphragm is 214.3 grams per square meter.

[0038] It operates at a working temperature of 90℃, with a potassium hydroxide electrolyte of 25% by mass, a DC voltage of 3.5V, and a DC current of 750A, and can operate continuously for more than 780 hours.

[0039] Comparative Example 1: Based on Example 1, the raw material was adjusted to use pure polyphenylene sulfide resin, while the rest of the technical solutions remained unchanged.

[0040] Comparative Example 2: Based on Example 1, the process of preparing nano-modified polyphenylene sulfide resin was adjusted so that no graphene was added, while the rest of the technical solutions remained unchanged.

[0041] test: The initial tensile strength of the example and comparative specimens (both 10cm × 20cm) was tested according to the test method in GB / T3923.1. The samples from the examples and comparative examples were placed in a hot air oven at 220°C for rapid thermal aging tests, which lasted for 280 hours. After the tests, the tensile strength of each sample was measured, and the strength retention rate (%) was calculated. Strength retention rate (%) = Fabric strength after heat treatment (N) / Fabric strength before heat treatment (N); Table 1

[0042] As can be seen from Table 1, the composite fiber fabric water electrolysis membrane prepared by the present invention has excellent heat aging resistance.

[0043] Contact angle measurement method: The hydrophilicity of the example and comparative sample specimens was tested using a JYSP-180 dynamic contact angle measuring device. Table 2

[0044] As can be seen from Table 2, the composite fiber fabric water electrolysis membrane prepared by the method of the present invention has excellent hydrophilic properties.

[0045] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A composite fiber fabric type water electrolysis diaphragm, characterized in that, It is made of sheath-core composite polyphenylene sulfide fiber through weaving; The core-sheath composite polyphenylene sulfide fiber includes a core bundle and a sheath layer, wherein the mass ratio of the core bundle to the sheath layer is 3:

1. The core-sheath composite polyphenylene sulfide fiber is formed by two-component melt spinning. The core bundle is made of polyphenylene sulfide resin; The skin layer is made of nano-modified polyphenylene sulfide resin; The method for preparing the nano-modified polyphenylene sulfide resin is as follows: (1) First, prepare a hexadecyltrimethylammonium bromide solution; (2) Add 16-20g of nano silica to 50-54mL of cetyltrimethylammonium bromide solution, stir for 10min at room temperature, and then sonicate for 5min to obtain a dispersion. (3) Mix 38-40g of polydimethylsiloxane, 13-15g of hydrogen-containing silicone oil and 1-1.5g of graphene, stir and mix at 1200r / min for 20min at 60℃, cool to obtain the mixture; (4) Add the dispersion and the mixture to the reactor at a mass ratio of 1.2:1, keep warm and stir for 10 min, then add 0.2-0.3 g of catalyst, adjust the temperature to 50℃ under an inert atmosphere, continue stirring and reacting for 20 hours, then filter, wash and dry to obtain nanocomposite material; (5) The nanocomposite material, coupling agent and polyphenylene sulfide resin obtained above are mixed and then added to a twin-screw extruder for melt extrusion granulation to obtain nano-modified polyphenylene sulfide resin. In step (5), the mass fraction of the nanocomposite material in the nano-modified polyphenylene sulfide resin is 1-1.8%. The coupling agent has a mass fraction of 0.2-0.3%; The coupling agent is vinyltrimethoxysilane.

2. The composite fiber fabric type water electrolysis diaphragm according to claim 1, characterized in that, The concentration of the hexadecyltrimethylammonium bromide solution in step (1) is 0.35-0.4 mol / L.

3. The composite fiber fabric type water electrolysis diaphragm according to claim 1, characterized in that: The frequency of the ultrasound in step (2) is 40 kHz.

4. The composite fiber fabric type water electrolysis diaphragm according to claim 1, characterized in that: The catalyst mentioned in step (4) is a chloroplatinic acid catalyst; The inert atmosphere is a nitrogen atmosphere.

5. A method for preparing a composite fiber fabric type water electrolysis membrane, used to prepare the composite fiber fabric type water electrolysis membrane as described in any one of claims 1-4, characterized in that: The process involves metering, opening and mixing, carding into a web, hydroentangling the front and back of the web, drying, and winding to obtain a composite fiber fabric type electrolytic membrane. Hydroentangling pressure 150-200 bar; The weight of composite fiber fabric type water electrolysis diaphragm is 180-250 grams per square meter.

Citation Information

Patent Citations

  • Ultrathin composite diaphragm for alkaline water electrolysis, preparation method of ultrathin composite diaphragm and alkaline water electrolysis device

    CN115896863A